1991
DOI: 10.1128/jvi.65.4.1735-1742.1991
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus type 2 VAI RNA transcription by polymerase III is blocked by sequence-specific methylation

Abstract: Sequence-specific methylation of the promoter and adjacent regions in mammalian genes transcribed by RNA polymerase II leads to the inhibition of these genes. So far, RNA polymerase ITT-transcribed genes have not been investigated in depth. We therefore studied methylation effects on the RNA polymerase ITTtranscribed VAI gene of adenovirus type 2 DNA. The VAI gene contains 20 5'-CG-3' dinucleotides, of which 4 (20%) can be methylated by Hpall (5'-CCGG-3') and Hhal (5'-GCGC-3'). Three of these 5'-CG-3' sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
5
20
0
Order By: Relevance
“…Methylation appears to have a different impact on polymerase III genes transcription according to the nature of their promoter sequences. The plant results with Brassica SINE S1 and Arabidopsis 5S rRNA genes are in agreement with mammalian reports, where SINEs (Liu and Schmid, 1993), viral genes (Juttermann et al, 1991) and tRNA Lys gene transcription (Besser et al, 1990) were inhibited by methylation, although the transcription of a Xenopus 5S rRNA gene was not (Besser et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Methylation appears to have a different impact on polymerase III genes transcription according to the nature of their promoter sequences. The plant results with Brassica SINE S1 and Arabidopsis 5S rRNA genes are in agreement with mammalian reports, where SINEs (Liu and Schmid, 1993), viral genes (Juttermann et al, 1991) and tRNA Lys gene transcription (Besser et al, 1990) were inhibited by methylation, although the transcription of a Xenopus 5S rRNA gene was not (Besser et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The impact of DNA methylation on pol III transcription is not clear and relies on a small number of reports, all of which (except The Plant Journal (2002) 29 (3), 313±323 ã 2002 Blackwell Science Ltd one in Brassica) use animal systems. Most of these studies were done on mammalian SINEs (Liu and Schmid, 1993), viral genes (Juttermann et al, 1991) and a tRNA Lys gene (Besser et al, 1990), and report a more-or-less severe transcriptional inhibition following methylation. In Brassica, using an in vitro assay, Arnaud et al (2001) reported a transcriptional inhibition that is directly correlated to the level of the template methylation (a Brassica SINE).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, effects of methylation on the transcription of Alu repeats and tRNA genes were not detected in in vitro transcription assays (5,20). However, in a recent study (21), the effects of methylation on the in vitro transcription of the VAI RNA gene were reliably detected at lower template concentrations than those employed in these previous studies. Methylation inhibits transcription of this gene both in vivo and in vitro.…”
Section: Regulated Methylation Of Alu Repeatsmentioning
confidence: 66%
“…Here we used low rather than high template concentrations, nuclear rather than cytoplasmic extracts, very CpG rich young Alu templates rather than a single older Alu, and either general methylation by CpG methylase or methylation targeted specifically to the A box rather than the untargeted methylation of a few restriction sites. While each of these technical differences undoubtedly contributes somewhat to the detection of methylation induced repression, the use of low template concentrations is critical (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation